Schwartz-Jampel Syndrome: a paediatric dentistry approach - Ana Paula Silveira Turrioni; Sarah Ayumi Sakima; Elisa Maria Aparecida Giro (Brazilian Dental Science)
Schwartz-Jampel syndrome (SJS) is a rare recessive disorder characterized mainly by myotonia. As the clinical signs and symptoms are manifested in the oromaxillofacial region, paediatric dentists may be first choice of parents that seek information and assistance to their children. A female patient diagnosed with SJS was brought to our clinic for dental treatment with main complain of difficulty on oral hygiene and mastication due to tooth crowding. The treatment included preventive measures, extraction of a supernumerary tooth and the maxillary primary second molars. Furthermore, the patient was referred to orthodontic treatment for correction of tooth crowding. When dealing with children with confirmed diagnosis of SSJ, paediatric dentists should be understand the need of planning the dental treatment considering the characteristics and possible complications associated with the syndrome in order to reduce the risks to patients, especially when surgical procedures are necessary.